The Adventures of Amaru: Integrating Learning Tasks Into a Digital Game for Teaching Children in Early Phases of Literacy - de Souza, Gilberto Nerino; Brito, Yvan Pereira dos Santos; Tsutsumi, Myenne Mieko Ayres; Marques, Leonardo Brandão; Goulart, Paulo Roney Kilpp; Monteiro, Dionne Cavalcante; Santana, Ádamo Lima de (Frontiers in Psychology, 2018)
In low-income countries, the history of academic failure is a liability for children acquiring literacy skills. It is thus important to develop strategies that motivate and focus these students on specific strategies to learn to read. Digital games can be useful in motivating students and assisting teachers in the teaching-learning process, but there are few interactive tools that effectively integrate tasks of direct instruction and good gameplay. This technical report describes an interactive digital game to engage students in the initial phase of reading skills acquisition, whose design incorporates evidence-based procedures. The game, called ‘The Adventures of Amaru’, aims to promote word coding-decoding skills and vocabulary growth through teaching trials. We discuss the adaptation of reading teaching curricula, their limitations and future implications of the use of this game by children from a low-income background.